Alternatif Model Kerjasama Build Operate Transfer Pada Pengelolaan Rest Area Jalan Tol - Radhian Fiqi Sayoga (Jurist-Diction, 2021)
AbstractThe construction of the toll road itself must be based on the Toll Road Concession Agreement which is handled by the Toll Road Regulatory Agency (BPJT) and the Toll Road Business Entity (BUJT). BPJT gives the authority to BUJT to work on toll roads and the section of toll roads. In every toll road construction it is required for BUJT to build a toll road rest area in accordance with what is mandated in Government Regulation No. 15/2005 concerning Toll Roads. BUJT in managing the Rest Area can be done by self-management or by collaborating with partners or investors. In collaborating with partners there are alternative methods of collaboration, namely with Build Operate Transfer and Build Operate Own. This method of cooperation will later be outlined in the Toll Road Rest Management Cooperation Agreement which must refer to Government Regulation Number 15 of 2005 concerning toll roads and Minister of Public Works and Public Housing Regulation No.1 / PRT / M / 2017 Regarding Procedures for Implementing Agency Procurement Business for concession of toll roads and refers to the legal requirements of the agreement.Keywords: Toll Road Concession; Build Operate Transfer; Toll Road Rest Management Agreement.AbstrakPembangunan jalan tol sendiri harus berdasar pada Perjanjian Pengusahaan Jalan Tol yang ditantangani oleh Badan Pengatur Jalan Tol (BPJT) dan Badan Usaha Jalan Tol (BUJT). BPJT memberi kewenangan kepada BUJT untuk mengusahaakan jalan tol dan ruas jalan tol. Dalam setiap pembangunan Jalan Tol di haruskan bagi BUJT untuk membangun Rest Area jalan tol sesuai dengan apa yang diamanatkan dalam Peraturan Pemerintah Nomor 15 Tahun 2005 Tentang Jalan Tol. BUJT dalam melakukan Pengelolaan Rest Area tersebut dapat dilakukan dengan swakelola maupun dengan cara melakukan kerjasama dengan mitra atau investor. Dalam melakukan kerjasama dengan mitra terdapat alternatif metode kerjasama yaitu dengan Build Operate Transfer dan Build Operate Own. Metode kerjasama ini nantinya akan dituangkan dalam Perjanjian Kerjasama Pengelolaan Rest Area Jalan Tol yang harus berpedoman pada Peraturan Pemerintah Nomor 15 Tahun 2005 tentang jalan tol dan Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat No.1/PRT/M/2017 Tentang Tata Cara Pelaksanaan Pengadaan Badan Usaha Untuk Pengusahaan Jalan Tol serta mengacu pada syarat sah perjanjian. Kata Kunci: Pengusahaan Jalan Tol; Build Operate Transfer; Perjanjian Pengelolaan Rest Area Jalan Tol.